(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article provides information about the epizootological status of fish liguliosis in water bodies in Pastdargom, Akdarya and Kattakurgan districts of Samarkand region and veterinary-sanitary expertise of fish meat affected by this disease.